Modulation of Abiotic Stress Responses in Rice by E3-Ubiquitin Ligases: A Promising Way to Develop Stress-Tolerant Crops - Melo, Fredilson Veiga; Oliveira, M. Margarida; Saibo, Nelson J. M.; Lourenço, Tiago Filipe (Frontiers in Plant Science, 2021)
Plants are unable to physically escape environmental constrains and have therefore evolved a range of molecular and physiological mechanisms to maximize survival in an ever-changing environment. Among these, the post-translational modification ubiquitination has emerged as an important mechanism to understand and improve stress response. The ubiquitination of a given protein can change its abundance (through degradation), alter its localization, or even modulate its activity. Hence, ubiquitination increases the plasticity of the plant proteome in response to different environmental cues and can contribute to improve stress tolerance. Though ubiquitination is mediated by different enzymes, in this review, we focus on the importance of E3-ubiquitin ligases, which interact with the target proteins and are, therefore, highly associated with the mechanism specificity. We discuss their involvement in abiotic stress response and place them as putative candidates for ubiquitination-based development of stress-tolerant crops. This review covers recent developments in this field using rice as a reference for crops, highlighting the questions still unanswered.